The genus Eustigmaeus Berlese (Acari: Stigmaeidae) from Greece - Stathakis, Theodoros I.; Kapaxidi, Eleftheria V.; Papadoulis, Georgios Th. (Zootaxa, 2016)
The present study summarizes the previous limited knowledge on the genus Eustigmaeus from Greece. Based on material collected from many localities, nine species are recorded from Greece for the first time and four species, Eustigmaeus irregularis sp. nov., E. fantinoui sp. nov., E. microvacuolatus sp. nov., and E. capitatus sp. nov. are described as new to science. Additionally, males of five known species of Eustigmaeus are described for the first time. A list of the world species of the genus Eustigmaeus and a key to species of this genus recorded in Greece are provided.